(untitled) (Research, Society and Development, 2022)
Objective: to identify, through the scientific literature, studies that address the role of nurses in the care of patients with COVID-19 in an adult Intensive Care Unit. Method: this is an integrative literature review with a time cut selected between the years 2020 to 2021; the databases used were SciELO, LILACS and PUBMED. Results: after applying the inclusion and exclusion criteria, the study sample consisted of 11 articles, 54.5% of them were published in 2020, while 45.4% were published in 2021, where these studies addressed aspects such as leadership of the nurse in front of the team as a facilitator of knowledge for a better offer of care in ICU COVID and empowerment of the profession through SAE. Conclusion: by carrying out this review, it was possible to analyze the main characteristics of the professional nurse’s performance in the face of patient care with COVID-19 located in the ICU.